2011
DOI: 10.1097/scs.0b013e3182108f4f
|View full text |Cite
|
Sign up to set email alerts
|

Sialolithiasis of the Submandibular Gland

Abstract: Sialolithiasis of the salivary gland is a benign pathology that occurs most frequently in the submandibular gland because of its anatomic features. Depending on the sialolith size and calcification degree, it can be visible in radiographic examinations. Commonly, patients may experience pain and/or edema, when the ducts are obstructed. The authors report the case of sialolithiasis of the submandibular gland in a 42-year-old, female, white-skinned patient, noticed during routine dental examination. Following di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 22 publications
0
24
0
6
Order By: Relevance
“…Some authors have reported that submandibular sialolithiasis causes a reduction of the salivary flow 15 , while others as Gaetti et al state that salivary flow is increased due to glandular enlargement 6,16 . In the present case, despite that a sialometry was not performed to check if there was a reduction of the salivary flow, no clinical or symptomatic evidence of changes or alterations occurred in the flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported that submandibular sialolithiasis causes a reduction of the salivary flow 15 , while others as Gaetti et al state that salivary flow is increased due to glandular enlargement 6,16 . In the present case, despite that a sialometry was not performed to check if there was a reduction of the salivary flow, no clinical or symptomatic evidence of changes or alterations occurred in the flow.…”
Section: Discussionmentioning
confidence: 99%
“…The submandibular gland is more susceptible to sialolithiasis (60%) 5 , due to its anatomy and physiology, since saliva is alkaline and has a higher concentration of calcium, phosphate and mucin, which may cause the appearance of foreign bodies in the walls of excretory ducts, contributing to the development of salivary stones 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Bununla birlikte çıkarılamayan nunun akışını yavaşlatır. Sekresyonun yerçekimine zıt yönde akması, içeriğinin daha alkali olması ve musinden, proteinlerden, kalsiyum ve fosfattan zengin olması sialolitlerin oluşmasına zemin hazırlayan faktörlerdir (1,18,31,32,34,35,36).…”
Section: şEkilunclassified
“…Além disso, pode haver a diminuição do fluxo salivar, aumento de volume local e, nos casos mais graves, disfagia 3,7 . Segundo Jardim et al 8 os exames de imagem que podem ser utilizados para verificar os cálculos salivares são as radiografias convencionais. As radiografias panorâmicas e oclusais apresentam precisão e acurácia satisfatória na detecção dos sialolitos 9 .…”
Section: Introductionunclassified